FOREWORD - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2017)
After a year in which Romania achieved the fastest growing economy in the European Union, 2017 comes with a unique set of challenges. In 2016, the economy was the main driver of consumption and economic analysts expect it to slow down, while prices will increase. The government estimated an increase of 5% for the Romanian economy in 2017, but the World Bank warns that this could be too optimistic and expects an advance of only 3.4% of the economy. However, growth remains above the EU average, which is why 2017 could be a year at least as good as 2016. ...